Chronic Wasting Disease: State of the Science - Jason C. Bartz; Rebeca Benavente; Byron Caughey; Sonja Christensen; Allen Herbst; Edward A. Hoover; Candace K. Mathiason; Debbie McKenzie; Rodrigo Morales; Marc D. Schwabenlander; Daniel P. Walsh; the NC1209: North American Interdisciplinary Chronic Wasting Disease Research Consortium Members (Pathogens, 2024)
Chronic wasting disease (CWD) is a prion disease affecting cervid species, both free-ranging and captive populations. As the geographic range continues to expand and disease prevalence continues to increase, CWD will have an impact on cervid populations, local economies, and ecosystem health. Mitigation of this “wicked” disease will require input from many different stakeholders including hunters, landowners, research biologists, wildlife managers, and others, working together. The NC1209 (North American interdisciplinary chronic wasting disease research consortium) is composed of scientists from different disciplines involved with investigating and managing CWD. Leveraging this broad breadth of expertise, the Consortium has created a state-of-the-science review of five key aspects of CWD, including current diagnostic capabilities for detecting prions, requirements for validating these diagnostics, the role of environmental transmission in CWD dynamics, and potential zoonotic risks associated with CWD. The goal of this review is to increase stakeholders’, managers’, and decision-makers’ understanding of this disease informed by current scientific knowledge.